Coastal Sediment Transport Study along Shoreline by using Smooth Particle Hydrodynamics - Zawawi M.H.; Azman A.; Radzi M.R.M.; Abas A.; Aziz N.A. (Institute of Physics Publishing, 2023)
Sediment transport typically due to combination of gravity acting on the sediment, and/or the movement of the fluid in which the sediment is entrained. This paper gives an exposure simulation of three-dimensional (3D) sediment transports by using Smooth Particle Hydrodynamics (SPH) at coastal area. The SPH formulation from Monaghan constructed in the code is modified according to the desired model to be solved. The code is then computed by using single Graphics Processing Unit (GPU) with 14 cores multiprocessors. The behavior of sediment transport is investigated in this research based on Herschel-Bulkley-Papanastasiou (HBP) model. A constant sinewave of 0.5sin(0.5?t) is applied to the fluid domain to create sea wave effect that will cause sediment transport. The results show that the goal to get sediment transport is achieved and for the further study, the rate of erosion and accretion can be determined to give more meaningful and valuable to the result. Published under licence by IOP Publishing Ltd.